Fractal morphology, imaging and mass spectrometry of single aerosol particles in flight - Loh, Ne-Te Duane; Lomb, Lukas; Steinbrener, Jan; Shoeman, Robert L.; Kassemeyer, Stephan; Epp, Sascha W.; Erk, Benjamin Michael Dieter; Rolles, Daniel; Rudenko, Artem; Rudek, Benedikt; Foucar, Lutz Michael; Ullrich, Joachim; et al. (Nature, 2012)
The morphology of micrometre-size particulate matter is of critical importance in fields ranging from toxicology1 to climate science2, yet these properties are surprisingly difficult to measure in the particles’ native environment. Electron microscopy requires collection of particles on a substrate3; visible light scattering provides insufficient resolution4; and X-ray synchrotron studies have been limited to ensembles of particles5. Here we demonstrate an in situ method for imaging individual sub-micrometre particles to nanometre resolution in their native environment, using intense, coherent X-ray pulses from the Linac Coherent Light Source6 free-electron laser. We introduced individual aerosol particles into the pulsed X-ray beam, which is sufficiently intense that diffraction from individual particles can be measured for morphological analysis. At the same time, ion fragments ejected from the beam were analysed using mass spectrometry, to determine the composition of single aerosol particles. Our results show the extent of internal dilation symmetry of individual soot particles subject to non-equilibrium aggregation, and the surprisingly large variability in their fractal dimensions. More broadly, our methods can be extended to resolve both static and dynamic morphology of general ensembles of disordered particles. Such general morphology has implications in topics such as solvent accessibilities in proteins7, vibrational energy transfer by the hydrodynamic interaction of amino acids8, and large-scale production of nanoscale structures by flame synthesis9.